15. Solli: Boplass fra mellommesolitikum med gjenbruk i flere perioder - Oppvang, Janne; Ilson, Paul (Tromura, 2025)
At Solli, 14 structures were investigated, interpreted as remnants of settlements from various periods of the Stone Age. The site was reused multiple times over an extended period, with datings ranging from 7000 BC to AD 400.The majority of the finds can be associated with the Middle and Late Mesolithic, featuring blade technology and pressure blade techniques.
Keywords: Archaeological excavation; Middle Mesolithic; Early stone age; settlement; reuse; House Pits; Blades; pressure blade technology